Alkylation and aldol reactions of acyl derivatives of N-1-(1 '-naphthyl)ethyl-O-tert-butylhydroxylamine: asymmetric synthesis of alpha-alkoxy-, alpha-substituted-beta-alkoxy- and alpha,beta-dialkoxyaldehydes - Chernega, A; Davies, S; Fletcher, A; Goodwin, C; Hepworth, D; Prasad, R; Roberts, P; Savory, E; Smith, A; Thomson, J (2010)
Treatment of a range of O-protected glycolate derivatives of the chiral auxiliary N-1-(1′-naphthyl)ethyl-O-tert-butylhydroxylamine with KHMDS in the presence of 18-crown-6 followed by addition of an alkyl halide generates α-substituted derivatives with very high levels of diastereoselectivity. Alternatively, reaction of the potassium enolate of a propanoate or O-protected glycolate derivative of N-1-(1′-naphthyl)ethyl-O-tert-butylhydroxylamine with a range of aldehydes gives syn-aldol products with high levels of diastereoselectivity. These adducts may be reductively cleaved with LiAlH4 to give enantiopure α-alkoxy-, α-substituted-β-alkoxy- and α,β-dialkoxyaldehydes in good yield. © 2010 Elsevier Ltd. All rights reserved.